Inside the borders but outside the box: An immersion program aligned with the PRME and the SDG to foster reflexivity. Issue 3 (November 2019) - Wood, Thomaz; Pansarella, Laura
Abstract: How can reflexivity be fostered among future managers? This article presents the dynamics and impacts of an immersion program used by a business management and public administration school based in São Paulo, Brazil, for 13 years. Every year, students conduct research for 20–30 days on public, social, and private organizations, coordinating projects focused on economic and social development and promoting citizenship. These projects occur in poor regions far from the largest urban centers in Brazil. After visiting areas and situations within the country's borders that are unknown to them, the students bring their experiences back to the classroom to be analyzed, recorded, and shared. We evaluated the impact of this program on the participants and observed the following: prejudices and stereotypes were reconsidered; a richer and more complex view of reality was achieved; and new ways of acting in the world were adopted. We argue that immersion in social projects fosters reflexivity, and we encourage fellow educators to consider adopting transdisciplinary programs of this type as a teaching strategy to educate reflexive managers and to prepare them for work and life. Highlights: Every year, students conduct research for 20–30 days on public, social, and private organizations. The program's original objective was to foster citizenship and expand its participants' vision of the world. When faced with different realities, students rethink prior ideas. Changes in attitudes and behaviors are nourished by stronger empathy for other individuals. Educating for reflexivity means sensitizing students to arouse their ethical responsibilities.